2a - 3b = -11
+ a + 3b = 8
---------------------
3a = -3
a = -1
b = 3
2006-12-12 05:40:49
·
answer #1
·
answered by feanor 7
·
0⤊
0⤋
simple: 2a-3b=-11
+ a+3b=8
----------------
2a + a -3b +3b = -3, therefore:
3a= -3, therefore a = -1.
2 (-1) -3b= -11
-2 -3b= -11
-3b = -9
b= -9/-3
b= 3
therfore: a +3b=8
-1 + 3(3)=8
8=8, TRUE
and: 2a-3b=-11
2(-1) -3(3)= -11
-2 - 9 = -11
-11 = -11, TRUE
2006-12-12 13:52:00
·
answer #2
·
answered by mike c 2
·
0⤊
0⤋
first u add the both equations
2a - 3b = -11
a + 3b = 8
-------------------
3a = -3 nu u see the unknown b is eleminated and we have goten the value of a = -1
nu put the value of a in any given equation
(-1) + 3 b = 8
so 3 b = 9 and u have b = 3
pls donot ask so simple questions on web, thanx
2006-12-12 13:46:35
·
answer #3
·
answered by d_aries1987 1
·
0⤊
0⤋
add the two equtions together:
2a-3b = -11
1a+3b = 8
___________
3a+0b = -3
so a = -1.
Then use a = -1 to solve for b:
a+3b = 8
-1+3b = 8
3b = 9
so b = 3
2006-12-12 13:44:01
·
answer #4
·
answered by ? 1
·
0⤊
0⤋
ok, first put one equation below the other like
2a-3b=(-11)
+ a+3b=8
----------------------and then add them...u will see that b cancels
3a=(-3)
a=(-1)
then, plug a=(-1) back into either equation (I'll choose the first)
2(-1)-3b=(-11)
(-2)-3b=(-11)
-3b=(-9)
b=3
then plug them both back into either equation to check(i'll choose the second this time)
a+3b=8 a=(-1) b=3
-1+3(3)=8
TRUE, ur good!
hope that helped!
2006-12-12 13:40:16
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋
2a - 3b = -11............(1)
a + 3b = 8 ...............(2)
(1) + (2) => 2a - 3b + a + 3b = -11 + 8
3a = -3 => a=-1
and replacing a in (1) we get
-2 -3b = -11
-3b = -9
b = 3
2006-12-12 13:48:29
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
a + 3b = 8
- 3b -3b
a=8-3b
2a - 3b = -11
2(8-3b) - 3b = -11
16 - 6b - 3b = -11
16-9b = -11
-16 -16
-9b = -27
b=3
2006-12-12 13:46:28
·
answer #7
·
answered by strtat2 5
·
0⤊
1⤋